Nutritional rehabilitation of special cases of malnourished children aged 0 to 6 months at the Maradi Regional Hospital, Niger - Amadou, Issoufou; Hamadou, Mazou; Samna Soumana, Oumarou (Indian Journal of Child Health, 2024)
Malnutrition is a pathological state resulting from the relative or absolute deficiency or excess of one or more essential nutrients, whether this state manifests itself clinically, or whether detectable only by biological, anthropometric, or physiological analyses. This study uses a cross-sectional survey conducted on a representative sample of 60 mothers with their children aged 0–6 months (special cases) admitted at the Intensive Nutritional Education and Recovery Center of the Maradi Regional Hospital from May 23 to July 23, 2022. The main objective of this study is to evaluate the nutritional rehabilitation of children in special cases within this service. Data collection was done on 60 children with severe acute malnutrition. A questionnaire was addressed to the mothers of malnourished children. The hospital records were also used to access information on the anthropometric parameters, thus determining the nutritional status of the children studied. The study results show that children aged 0–3 months are the most affected by malnutrition and are special cases with a weight/height ratio below minus 3 z-score. They most often suffer from diarrhea with a rate of 41.6% and fever with a rate of 21.7%. These children generally come from parents with no schooling and with limited resources. It can also be noted that most of these malnourished children come from mothers who practiced mixed breastfeeding. To get done, during treatment, the majority of patients have to use the diluted F100 as the type of diet and a mode of feeding with the cup. The supplementary suckling technique was applied to get heal the special cases in need. In conclusion, the study affirms that socioeconomic and environmental factors play a very important role in the persistence of malnutrition in this part of the world.